A Case Report and Literature Review of Primary Central Nervous System Lymphoma in a Patient with Crigler–Najjar Syndrome: How We Managed - Maheshwari, Udip; Morzaria, Disha; Jagiasi, Seema; Maniar, Vashishth; Joshi, Ashish; Soneji, Sameer (Indian Journal of Medical and Paediatric Oncology, 2023)
Primary central nervous system lymphoma (PCNSL) is a rare form of CNS tumor that can be managed with curative intent using high-dose chemotherapeutic drugs. High-dose methotrexate is an essential drug for the management of PCNSL. We present a case of a 26-year-old man with a known comorbidity of Crigler–Najjar syndrome type II and a baseline bilirubin of 13.5 mg/dL, presented with somnolence and ataxia. In view of hyperbilirubinemia, the optimal treatment for CNS lymphoma, the De Angelis protocol, was modified for this patient. The patient tolerated the chemotherapy well with manageable fluctuations in bilirubin levels, followed by consolidation with whole-brain radiotherapy. He remains asymptomatic 6 months after the onset of the symptoms with the disease in complete remission. We highlight here this unusual case of PCNSL where high-dose methotrexate was used with close observation of liver function in view of hyperbilirubinemia in a known case of Crigler–Najjar syndrome.
Keywords: Crigler–Najjar syndrome; DeAngelis protocol; hyperbilirubinemia; primary CNS lymphoma